Ayurvedic science of food and nutrition - Rastogi, Sanjeev (Springer New York, 2014)
Ayurveda is widely considered to be one of the oldest health care traditions still in practice today. Originating in India over 3,000 years ago, it is now increasingly recognized and practiced globally including in many European countries and the United States. Food and nutrition play a crucial role in the health care wisdom of Ayurveda. The Ayurvedic Science of Food and Nutrition discusses the various principles of healthy eating as prescribed by Ayurveda. Divided into three sections, it addresses the fundamentals, the clinical applications, and the future challenges of Ayurveda. Specifically, the book discusses issues such as the concept of diet, the use of food as medicine, especially to treat diabetes and cancer, convalescent food practices, and fasting therapy. The Ayurvedic Science of Food and Nutrition is unique in that it is one of the only books to investigate the scientific rationale behind Ayurveda, enabling this health care tradition to potentially be incorporated into a Western clinical practice model when this latter conventional therapy is found to be ineffective.   About the Editor Sanjeev Rastogi is associate professor at the State Ayurvedic College and Hospital of Lucknow University, in Lucknow, India.